Design and Application of a Battery Aging Test Bench - Gungor, Fikri Samet; Boynuegri, Ali Rilat; Saray, Merve (IEEE, 2024)
With the increasing importance of energy storage systems (ESS) in integrating renewable energy sources, optimizing grid stability, and providing backup power during outages, the need for reliable and durable batteries has never been greater. This research aims to answer critical questions such as how batteries age over time, when their performance declines, and how durable they are for long-term use. The study's primary objective is to design a device that performs cycle aging tests more effectively to evaluate battery performance and durability. This device will facilitate faster, more accurate, and less costly battery testing. By conducting controlled aging tests, the study aims to provide valuable insights into the aging process of lithium-ion batteries (LIB), helping to optimize their performance and extend their lifespan. The development of this test device could significantly enhance the understanding of battery aging mechanisms, ultimately contributing to the advancement of battery technology and its applications. Future works will discuss the design and methodology of the aging test device, present the results of the aging tests, and analyze the implications of these findings for future battery development This information will help detect energy quality problems when batteries are reused in secondlife applications (SLA).
Keywords: Aging; Battery; Cycle Aging Test; Energy storage; CHARGE ESTIMATION; STATE; Energy & Fuels; Engineering